Research on Early Warning Model of Electric Vehicle Charging Safety. Issue 1 (June 2021) - Jiang, Linru; Zhang, Yuanxing; Li, Taoyong; Diao, Xiaohong; Zhang, Jing
Abstract: At present, an effective evaluation system of the charging safety of electric vehicles has not been formed and lacks the corresponding safety early warning and protection control measures. It is of great significance to ensure the charging safety of electric vehicles and promote the rapid development of electric vehicles. Through the analysis of the establishment of the electric vehicle charging safety evaluation index system, the establishment method of the index system is studied. Finally, the demand analysis of the electric vehicle charging safety early warning and protection system is carried out. The function of establishing safety evaluation model in the system is clarified. For the comprehensive demonstration operation of electric vehicle, it is verified that the electric vehicle charging safety warning and protection system has real-time warning and protection function for battery, charging equipment and distribution network, which embodies the practical engineering value of the system.